SEBERAPA MASIF PENGHINDARAN PAJAK MELALUI HARGA TRANSFER DAN TATA KELOLA PERUSAHAAN YANG TERDAFTAR DI BEI? - Veronika, Vera; Wardhani, Rulyanti Susi; Erwandy, Erwandy (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2024)
This study aims to analyze and demonstrate empirically the effect of transfer pricing, institutional ownership and managerial ownership on tax avoidance in manufacturing companies listed on Indonesia Stock Exchange in 2020-2021. The dependent variable in this study is tax avoidance, which is measured by ETR (Effective Tax Rate). The independent variables in this study are transfer pricing, institutional ownership and managerial ownership. The population in this study are all manufacturing companies listed on Indonesia Stock Exchange in 2020-2021. The sampling method in this study was purposive sampling with a final total samples of 26 companies. The data collection method used is a quantitative method with secondary data in the form of financial reports and annual reports of manufacturing companies listed on Indonesia Stock Exchange for 2020-2021. The method of data analysis in this study is the panel data regression analysis of the common effect model. The results showed that transfer pricing had a negative and significant effect on tax avoidance, institutional ownership had a negative and significant effect on tax avoidance and managerial ownership had a positive and significant effect on tax avoidance. Simultaneously, the three variables affect tax avoidance.